Richard T. Ely the story of economics in the United States - Warren J. Samuels (Research in the history of economic thought and methodology, 2002)
This work publishes for the first time Richard T. Ely's study of the history of American economic thought. Ely was both a reformer of economics and a leading economist between the 1880's and 1930's. A founder of the American economic association, he himself wrote on a vast number of topics. This history of American economics tells a story that is both straightforward and his own interpretation.